2010
DOI: 10.1073/pnas.1009346107
|View full text |Cite
|
Sign up to set email alerts
|

Development of the malaria parasite in the skin of the mammalian host

Abstract: The first step of Plasmodium development in vertebrates is the transformation of the sporozoite, the parasite stage injected by the mosquito in the skin, into merozoites, the stage that invades erythrocytes and initiates the disease. The current view is that, in mammals, this stage conversion occurs only inside hepatocytes. Here, we document the transformation of sporozoites of rodentinfecting Plasmodium into merozoites in the skin of mice. After mosquito bite, ∼50% of the parasites remain in the skin, and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 35 publications
5
110
0
8
Order By: Relevance
“…Presumably, transverse dermal cell movements by sporozoites (from the invasion of host cells that cause disruption of the plasma membrane) [9] are important for future establishment of liver stage infection, since it is the mechanism by which these parasites can escape from the dermal phagocytes [10]. More recently, it was reported that a small proportion of the dermal sporozoites can continue their development into merozoite forms (as they usually do inside liver cells) by infecting hair follicle cells [11]. Nonetheless, the contribution of these dermal merozoite forms compared to the entire host infection appears to be either inexistent or minimal [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Presumably, transverse dermal cell movements by sporozoites (from the invasion of host cells that cause disruption of the plasma membrane) [9] are important for future establishment of liver stage infection, since it is the mechanism by which these parasites can escape from the dermal phagocytes [10]. More recently, it was reported that a small proportion of the dermal sporozoites can continue their development into merozoite forms (as they usually do inside liver cells) by infecting hair follicle cells [11]. Nonetheless, the contribution of these dermal merozoite forms compared to the entire host infection appears to be either inexistent or minimal [11].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was reported that a small proportion of the dermal sporozoites can continue their development into merozoite forms (as they usually do inside liver cells) by infecting hair follicle cells [11]. Nonetheless, the contribution of these dermal merozoite forms compared to the entire host infection appears to be either inexistent or minimal [11]. Sporozoites injected by infected mosquitoes into actively immunized mice (animals pre-treated with irradiated sporozoites), or passively immunized animals (mice that received mAbs against sporozoites), stop moving and are rapidly destroyed [7,12], thereby inferring that immune system pre-activation by the first parasite inoculation can prevent future infections by new sporozoites.…”
Section: Introductionmentioning
confidence: 99%
“…When available, the tests are useful tools to investigate drug activity against pre-erythrocytic stages of the parasites , Mazier et al 2009). The use of GFP sporozoites would be useful in protocols because this approach would allow the parasite route to be followed from the site of inoculation to the liver cells (Gueirard et al 2010), thus elucidating where the parasite is targeted by the antimalarials. The anti-sporozoite activity of two medicinal plants, Ampelozyziphus amazonicus and Strychnopsis thouarsii, has been demonstrated; these drugs were used in malaria-endemic areas of Brazil (AndradeNeto et al 2008, Krettli et al 2001 and Madagascar (Carraz et al 2006), as discussed below.…”
Section: Malaria Treatment and Drug-resistant Parasites -mentioning
confidence: 99%
“…Cerca de 15 a 200 esporozoítos são injetados por um único mosquito infectado (AMINO et al, 2006;GUEIRARD et al, 2010;SILVIE et al, 2007). No sistema circulatório, após cerca de 60 minutos os esporozoítos invadem os hepatócitos, iniciando assim o ciclo exoeritrocítico.…”
Section: Bbr -Biochemistry and Biotechnology Reportsunclassified